Case Report: Rare Iliac Vein Compression (May–Thurner) Syndrome in a Pediatric Patient - Ji, Lianfu; Yang, Fan; Chen, Xuan; Chen, Jinlong; Cheng, Xueying; Yin, Jie; Qin, Yuming; Yang, Shiwei (Frontiers in Pediatrics, 2021)
Iliac vein compression syndrome (IVCS) or May-Thurner syndrome occurs predominantly in young to middle aged women. Here we reported a case of iliac vein compression syndrome in a 5-year-old boy. The child was admitted to our vasculocardiology deparment with left lower extremity swelling present for 1 month. Blood tests revealed coagulation routine and platelets in the normal ranges. Computer tomography angiography (CTA) and Magnetic resonance imaging (MRI) showed left common iliac vein become narrow before it entered the right common iliac vein. To further clarify, we performed angiography, which clearly showed the stenosis and the blood return of the iliac vein of the left common iliac vein. So Iliac vein compression syndrome was diagnosed. What is more, we found aorta descended to the right of spine and this may be the reason for the apparent compression of left common iliac vein. For the children was young and had mild symptoms, we treated the patient conservatively mainly including elevation of the affected limb, wearing medical elastic socks and oral aspirin for anticoagulation. The boy is followed-up closely, and stent placement may need to be considered in the future.